Expression of amyloid precursor-like protein 2 (APLP2) in glioblastoma is associated with patient prognosis - Chen, Yihong; Wang, Hongxiang; Tan, Cong; Yan, Yong; Shen, Junyan; Huang, Qilin; Xu, Tao; Lin, Junting; Chen, Juxiang (Folia Neuropathologica, 2018)
The purpose of this study was to investigate the expression status of amyloid precursor-like protein 2 (APLP2) and its clinical relevance in patients with glioblastoma. The publically available database Project Betastasis involving Repository for Molecular Brain Neoplasia Data (REMBRANDT) and The Cancer Genome Atlas (TCGA) was first utilized to analyze the expression and prognostic potential of APLP2 in glioblastoma. Compared with normal controls, the glioblastoma group from each dataset showed no significant difference of APLP2 expression (p > 0.05). However, when connected to glioblastoma patient’s prognosis, a high APLP2 expression was found to be associated with short overall survival in REMBRANDT cases (p = 0.0323) but not the TCGA group (p = 0.0578). Consistently, APLP2 expression detected by immunohistochemistry in our cohort revealed an undifferentiated expression pattern between glioblastoma (n = 114) and normal brain (n = 16) (p = 0.265) and among all grade gliomas. Furthermore, univariate and multivariate analyses identified a high APLP2 expression as an independent risk factor for overall survival (hazard ratio = 1.537, p = 0.041) and progression-free survival (hazard ratio = 1.783, p = 0.037) of glioblastoma patients. In conclusion, the expression of APLP2 might correlate with tumor development and be a prognostic factor for patients with glioblastoma.